Friends in Activities, School-related Affect, and Academic Outcomes in Diverse Middle Schools - Knifsend, Casey A. (J Youth Adolesc, 2018)
Participating in school-based activities is linked to positive academic engagement and achievement, but less is known about how peer relationships within activities affect these outcomes. The current study examined friends in extracurricular activities as a predictor of academic outcomes in multiethnic middle schools in California. Specifically, the mediating role of school belonging, and interactions by ethnicity and type of activity, were examined in a sample including African American or Black, East or Southeast Asian, White, and Latino youth in extracurricular activities (N = 2268; M(age)= 13.36 in eighth grade; 54% female). The results of multilevel mediational models suggested that school belonging mediated the link between friends in activities and academic outcomes, and these findings replicated across groups based on ethnicity and the type of activity in which one was involved in general. These results are discussed in terms of how activities can be structured to promote positive peer relations in ways that are linked with academic engagement and achievement.